Eye-tracking analysis of face observing and face recognition - Iskra, Andrej; Gabrijelčič Tomc, Helena (Journal of Graphic Engineering and Design, 2016)
Images are one of the key elements of the content of the World Wide Web. One group of web images are also photos of people. When various institutions (universities, research organizations, companies, associations, etc.) present their staff, they should include photos of people for the purpose of more informative presentation. The fact is, that there are many specifies how people see face images and how do they remember them. Several methods to investigate person’s behavior during use of web content can be performed and one of the most reliable method among them is eye tracking. It is very common technique, particularly when it comes to observing web images. Our research focused on behavior of observing face images in process of memorizing them. Test participants were presented with face images shown at different time scale. We focused on three main face elements: eyes, mouth and nose. The results of our analysis can help not only in web presentation, which are, in principle, not limited by time observation, but especially in public presentations (conferences, symposia, and meetings).